Oracle RMAN : pocket reference - Kuhn, Darl (O'Reilly, 2002)
Oracle RMAN Pocket Reference is a handy guide for DBAs who intend to use Oracle Recovery Manager for database backup and recovery. Because Recovery Manager (RMAN) is a relatively new tool, many DBAs are just becoming familiar with it. They will welcome a timely book that explains clearly and concisely how to use RMAN for common backup and recovery tasks that are infrequent, yet extremely vital. The first portion of the book is primarily task-oriented. After a short section on RMAN architecture, the book shows (in checklist style) how to perform common backup and recovery tasks such as.